Diagnostic value of abdominal follow-up sonography in polytrauma patients: a retrospective study - Lichtenstein, Thorsten; Chang, De-Hua; Sokolowski, M.; Große Hokamp, Nils; Berninger, Markus Thomas; Simons, R. M.; Hellmich, M; Maintz, David; Henning, Tobias Daniel (Medicine, 2020)
In many German trauma centres, it is routine to perform abdominal follow-up sonography (AFS) 6 h after admission for patients with multiple trauma, even if the clinical course is uneventful and multi-slice computed tomography (MSCT) reveals no abdominal pathology. However, this approach is not recommended in the German Guidelines for trauma, and recent studies have questioned the value of AFS to these patients. The present study aimed to evaluate the revised German Guidelines for trauma with respect to the omission of AFS. - We included patients with multiple injuries with no clinical signs of abdominal trauma and with normal abdominal MSCT. We collected clinical data of 370 consecutive patients who underwent AFS (Group A) and another 370 consecutive patients who did not undergo AFS (Group B). - No abdominal injury was missed by the omission of AFS, and thus, no patient suffered from its omission or benefitted from the use of AFS. In our study population, the negative predictive value of normal MSCT results combined with no clinical signs of abdominal trauma was 100% (95% confidence interval: 99.5%-100.0%). - This single-centre study conducted in a large German trauma centre demonstrates AFS to have no utility in the diagnosis of abdominal injury. Moreover, omission of AFS for conscious patients without clinical signs of abdominal trauma and with negative abdominal MSCT does not appear to have negative consequences in terms of missed abdominal injury. - Therefore, AFS can be safely omitted in the majority of cases of polytrauma, which simplifies the imaging workup tremendously.
Gesehen am 23.12.2020